Niobe w oku kamery. Projekt filmowy — między konkretyzacją a scenopisem: - - Michałowski, Piotr (Zagadnienia Rodzajów Literackich, 2019)
Niobe, a poem by Gałczyński was interpreted with verse and musical references, in the context of Mediterranean culture and contemporary realities of the palace of Nieborów, where a copy of the Ancient sculpture is located. The author creates a “film theory of narratology” and proceeds with reflections on various relationships between literature and cinema, on natural sight and imagination, and takes into consideration the following perspective theories: intersemiotic comparative, Bergson, Ingarden, Helman, Ziomek. Next, he offers a film interpretation of the descriptive part of the poem through a Large Violin Concert.